2001
DOI: 10.1002/mrd.1067
|View full text |Cite
|
Sign up to set email alerts
|

Capacitation dependent activation of tyrosine phosphorylation generates two sperm head plasma membrane proteins with high primary binding affinity for the zona pellucida

Abstract: The recognition and binding of sperm cells to the zona pellucida (the extracellular matrix of the oocyte) are essential for fertilization and are believed to be species specific. Freshly ejaculated sperm cells do not bind to the zona pellucida. Physiologically this interaction is initiated after sperm activation in the female genital tract (capacitation) via a yet unknown mechanism, resulting in the binding of a receptor in the apical sperm plasma membrane to the zona pellucida. In order to mimic this biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…Furthermore, the localization of phosphorylated proteins in the acrosome of capacitated sperm, together with its further loss after the acrosome reaction, could be related to the activation of certain proteins involved in this process (Dube et al 2005). Similarly, as reported in several mammalian species, zona pellucida binding induced phosphorylation in the midpiece (Leyton & Saling 1989, Flesch et al 2001) and other tail regions (Urner et al 2001.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, the localization of phosphorylated proteins in the acrosome of capacitated sperm, together with its further loss after the acrosome reaction, could be related to the activation of certain proteins involved in this process (Dube et al 2005). Similarly, as reported in several mammalian species, zona pellucida binding induced phosphorylation in the midpiece (Leyton & Saling 1989, Flesch et al 2001) and other tail regions (Urner et al 2001.…”
Section: Discussionmentioning
confidence: 62%
“…2C). The possibility of a relationship between plasma membrane phosphoprotein expression and zona binding has been alluded to in other mammalian species (Flesch et al, 1999;Flesch et al, 2001;Tardif et al, 2001). However, this is the first report of the appearance of tyrosinephosphorylated proteins on the surface of live mouse spermatozoa during capacitation.…”
Section: Discussionmentioning
confidence: 94%
“…Some of these techniques, however, tend to give low purifications and poorly defined fractions, or involve treatments that denature proteins, inhibit enzyme activity, or affect the functional integrity of the membranes. Careful evaluation of the strategy is especially relevant for proteins involved in ZP recognition; if the preparation contains acrosomal contamination, intra-acrosomal ZP-binding proteins will be identified that may mask primary (plasma membrane) ZP-binding proteins (14). An alternative to subcellular fractionation is enrichment in protein types from a whole cell lysate.…”
mentioning
confidence: 99%
“…Alternatively, immobilized lectins are used in affinity chromatography to extract surface glycoproteins (18), a method that can also be employed on nitrogen-cavitated and solubilized sperm plasma membrane material. Finally, sperm head plasma membrane proteins with high primary ZP binding affinity have been specifically isolated using ZP fragment columns (14,19).…”
mentioning
confidence: 99%